EFFECTS OF CREDIT RISK ON PERFORMANCE OF TRANSPORT FIRMS IN KENYA - Noor, Jamal Ali Mohamed; Njeru, Dr. Agnes; Muoria, Dr. Esther (IJRDO - Journal of Business Management, 2017)
The specific objective of this study was to establish the effect of credit risk on performance of transport firms in Mombasa County. The study employed triangulation (Mixed of quantitative and qualitative) research design. The target population was 2013 firms and the sample size was 172 firms arrived at through stratified and purposive sampling methods. The questionnaire was the primary data tool. The study found out that credit risk has significant effects on financial performance of transport firms in Kenya. It concludes that transport firms should maintain appropriate credit measurement, administration and monitoring. It recommends that managers of Transport firms should continuously ensure adequate controls over credit risk are put in place